2017
DOI: 10.1053/j.gastro.2017.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies TLL1 Variant Associated With Development of Hepatocellular Carcinoma After Eradication of Hepatitis C Virus Infection

Abstract: In a GWAS, we identified the association between the SNP rs17047200, within the intron of TLL1, and development of HCC in patients who achieved an SVR to treatment for chronic HCV infection. We found levels of Tll1/TLL1 mRNA to be increased in rodent models of liver injury and liver tissues of patients with fibrosis, compared with controls. We propose that this SNP might affect splicing of TLL1 mRNA, yielding short variants with high catalytic activity that accelerates hepatic fibrogenesis and carcinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 53 publications
2
92
1
Order By: Relevance
“…Previous studies have indicated that tolloid‐like protein 1 (TLL1) exerts several biological effects in regulating extracellular matrix assembly, and in transforming growth factor‐β signaling . We showed that TLL1 mRNA levels increased in human stellate cells with activation, and in liver tissues in rodent models and CHC patients according to the progression of hepatic fibrosis . Therefore, we presume that TLL1 might contribute to HCC development mainly through hepatic fibrogenesis.…”
Section: Hepatocarcinogenesismentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies have indicated that tolloid‐like protein 1 (TLL1) exerts several biological effects in regulating extracellular matrix assembly, and in transforming growth factor‐β signaling . We showed that TLL1 mRNA levels increased in human stellate cells with activation, and in liver tissues in rodent models and CHC patients according to the progression of hepatic fibrosis . Therefore, we presume that TLL1 might contribute to HCC development mainly through hepatic fibrogenesis.…”
Section: Hepatocarcinogenesismentioning
confidence: 85%
“…Two GWAS in Japanese cohorts identified genetic variants associated with the development of HCC in patients with chronic HCV infection . Furthermore, we recently conducted a GWAS for the development of HCC in Japanese CHC patients who had achieved SVR on IFN‐based therapy …”
Section: Hepatocarcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the glycomarker, host genetic variants would be useful for implementing a personalised surveillance of HCC in patients with HCV infection (13). A recent study revealed that a variant of the Tolloid-like 1 gene was a predictor for HCC development after the eradication of HCV (14). Although the effect of this variant must be further validated in other ethnic groups, it provided insights for future studies on the mechanisms of hepatocarcinogenesis after HCV eradication.…”
mentioning
confidence: 99%